Determinants of consumer online reviews / Mursyida Mahshar...[et al.] - Mahshar, Mursyida; Abu Hassan, Anita; Jaafar, Elias; Ramli⁴, Abd Rasyid; Mohd Isad, Nur Farahanum (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
Online reviews show consumer opinion or viewpoint about personal experience of using products that they have purchased or used. The review which is in the form of written comment or rating is posted on the web sites or social media which is publicly accessible. Online reviews could be seen in two conditions, before or after the consumption of goods. This paper is trying to find some empirical evidence on the factor selected against the online review on the post-condition. The primary data is collected from eighty respondents using stratified random sampling against the total population of hundred employees in commercial department, operations and production department at Kantar World Panel Malaysia. Regression analysis is used to analyse the strength level of each factor in influencing the changes in online reviews. The findings showed only purchase intention may influence the online review while the other two independent variables namely sales and product brand had no influence on the online review. The result could be used as important information whether online review may influence consumer buying decision.